A review of air quality, biological indicators and health effects of second-hand waterpipe smoke exposure. (5th December 2014) - Kumar, Sumit R; Davies, Shelby; Weitzman, Michael; Sherman, Scott
Abstract : Objective: There has been a rapid increase in the use of waterpipe tobacco and non-tobacco based shisha in many countries. Understanding the impact and effects of second-hand smoke (SHS) from cigarette was a crucial factor in reducing cigarette use, leading to clean indoor air laws and smoking bans. This article reviews what is known about the effects of SHS exposure from waterpipes. Data sources: We used PubMed and EMBASE to review the literature. Articles were grouped into quantitative measures of air quality and biological markers, health effects, exposure across different settings, different types of shisha and use in different countries. Study selection: Criteria for study selection were based on the key words related to SHS: waterpipe, hookah, shisha and third-hand smoke. Data extraction: Independent extraction with two reviewers was performed with inclusion criteria applied to articles on SHS and waterpipe/hookah/shisha. We excluded articles related to pregnancy or prenatal exposure to SHS, animal studies, and non-specific source of exposure as well as articles not written in English. Data synthesis: A primary literature search yielded 54 articles, of which only 11 were included based on relevance to SHS from a waterpipe/hookah/shisha. Conclusions: The negative health consequences of second-hand waterpipe exposure have major implications for clean indoor air laws and for occupational safety. There exists an urgent need for public health campaigns about the effects on children and household members from smoking waterpipe at home, and for further development and implementation of regulations to protect the health of the public from this rapidly emerging threat.